O2.3. INCREASED PROTEIN INSOLUBILITY IN BRAINS FROM A SUBSET OF PATIENTS WITH SCHIZOPHRENIA. (9th April 2019) - Nucifora, Leslie; MacDonald, Matthew; Lee, Brian; Peters, Matthew; Norris, Alexis; Orsburn, Benjamin Orsburn; Gleason, Kelly; Yang, Kun; Margolis, Russell; Pevsner, Jonathan; Tamminga, Carol; Sweet, Robert; et al.
Abstract: Background: The mechanisms leading to schizophrenia are likely to be diverse. However, there may be common pathophysiological pathways for subsets of the disease. In the present study, we hypothesized that disruption of protein quality control can lead to protein insolubility for a subset of patients with schizophrenia. Methods: Prefrontal cortex or superior temporal gyrus from autopsy brains provided by the University of Pittsburgh, University of Texas Southwestern, and Harvard were subjected to cold sarkosyl fractionation, separating proteins into soluble and insoluble fractions. All pellet samples were analyzed to quantify insoluble protein levels and ubiquitin reactivity, normalized to total homogenate protein. We then performed mass spectrometry analysis to identify the contents of the insoluble pellets. The potential biological relevance of the detected proteins was assessed using Gene Ontology Enrichment Analysis and Ingenuity Pathway Analysis. Results: A subset of patients with schizophrenia showed an increase in protein insolubility and ubiquitination in the insoluble protein fraction. Mass spectrometry of the insoluble fraction revealed that cases with increased insolubility and ubiquitination showed a similar pattern of peptide clustering by principal component analysis. The proteins that were significantly altered in the insoluble pellet were enriched for terms relating to axon target recognition as well as nervous system development and function. Discussion: This study suggests a pathological process related to protein insolubility for a subset of patients with schizophrenia. Understanding the molecular mechanism of this subtype of schizophrenia could lead to a better understanding of the pathways, circuitry, and symptoms seen in some patients with major mental illness and could lead to improved nosology and novel therapeutic targets.